Changes in bilateral tear film and corneal nerve stability in patients with unilateral neurotrophic keratitis - Wang, Fan; Li, Yue; Zhang, Zhaowei; Lu, Qiuchen; Shi, Cancan; Yu, Xiaofan; Hu, Fen; Li, Mingxin; Guo, Jianxin; Zhang, Zhenhao; Wang, He (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to examine the bilateral stability of the tear film in patients with unilateral neurotrophic keratitis and to observe changes in corneal nerve and immune cells under confocal microscopy.MethodsA prospective cross-sectional study included 63 patients with confirmed neurotrophic keratitis (NK) and 40 normal controls of similar sex and age. NK patients were divided into stage 1 and stage 2 based on the severity of the disease. Tear meniscus height (TMH), first non-invasive tear film break-up time (NIBUT-f), and corneal fluorescein staining were assessed. Corneal sensitivity was assessed using a Cochet-Bonnet esthesiometer. The corneal subbasal nerve plexus (SNP) and dendritic cells (DCs) were imaged using in vivo confocal microscopy (IVCM), and the SNP was analyzed using the fully automated corneal nerve analysis software “ACCmetric.”ResultsEyes with NK stage 2 showed worse performance in TMH, NIBUT-f, corneal fluorescein staining score, corneal sensitivity examination, SNP parameters, and DC density compared to NK stage 1 (all p < 0.001). The contralateral eyes of NK patients had significantly shorter NIBUT-f and higher dendritic cell density than controls (p < 0.001).ConclusionThe contralateral eyes of NK patients are more prone to dry eye signs than those of normal subjects and should be monitored and treated promptly. Increased dendritic cell numbers in the contralateral eyes of NK patients suggest bilateral immune alterations in unilateral disease.